2016
DOI: 10.1108/bfj-04-2016-0164
|View full text |Cite
|
Sign up to set email alerts
|

Organic consumers’ price knowledge, willingness-to-pay and purchase decision

Abstract: Purpose The purpose of this paper is to gain insights into organic consumers’ price sensitivity by investigating price knowledge, willingness-to-pay and real purchase decision. Design/methodology/approach Organic food consumers’ price knowledge, willingness-to-pay and real purchase decision were examined in a comprehensive field study with 642 respondents. An innovative method was used to collect data for products that were truly relevant to the respondents: before entering the shop, respondents were asked a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 36 publications
(57 reference statements)
1
27
0
8
Order By: Relevance
“…The positive and significant impact of this study can be interpreted: if price matches the quality, it will improve buying decisions. This study was in line with the research of Kuo and Nakhata (2016) and Rodiger et al (2016), but it was different from the two previous studies because, in the opinion of respondents, it placed price indicator that corresponded to the types of products which were considered to be most important to look at the price. The respondents argued that the definition of competitive price shows that the price must correspond to the features that the car has (Monroe, 2002;Eberhardt et al, 2009).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The positive and significant impact of this study can be interpreted: if price matches the quality, it will improve buying decisions. This study was in line with the research of Kuo and Nakhata (2016) and Rodiger et al (2016), but it was different from the two previous studies because, in the opinion of respondents, it placed price indicator that corresponded to the types of products which were considered to be most important to look at the price. The respondents argued that the definition of competitive price shows that the price must correspond to the features that the car has (Monroe, 2002;Eberhardt et al, 2009).…”
Section: Discussionsupporting
confidence: 82%
“…For example, Rodiger et al (2016) examined the effect of price on supermarket consumer's buying decision in Germany. The result shows that competitive price has a significant and positive effect on buying decisions.…”
Section: Price and Buying Decisionmentioning
confidence: 99%
“…As consumer demand for organic food has increased in the past two decades, researchers have extensively studied the purchase behavior associated with organic food (see [16] for a systematic review). This behavior, however, has very rarely been studied in a discount retailing context, but rather, from a price-sensitivity [17,18] or frugality [19] perspective. In a study that examined organic food in a discount retail setting, Gottschalk and Leistner [20] found that discount grocery shoppers tend to be more price-sensitive when buying organic food, whereas repeat buyers are more strongly influenced by other product characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in green field have showed that green product is usually premium priced in several countries (Taiwan in Teng & Lu, 2016;Tunisia in Salah et al, 2015;Scotland in Michaelidou & Hassan, 2008;etc.). For this reason, price is considered to be a barrier hindering the acquisition of green products (Marian et al, 2014;Rödiger et al, 2016). Walser & Nanopoulos (2007) stated that the more sensitive to green products' prices consumers are, the more unable they are to buy the products since these are more expensive than conventional counterparts.…”
Section: The Moderating Role Of Price Sensitivitymentioning
confidence: 99%